PENGEMBANGAN MODEL KOMUNIKASI DALAM PENGELOLAAN OBYEK WISATA - Chory Puspitasari; Paryudi Prayudi; Christina Rochayanti (Jurnal Paradigma, 2020)
The development of the Lava Tour Merapi tourism object is a special attraction for tourists, but in its management the regency tourism office faces obstacles from local residents who first managed the tourism object after the eruption of Mount Merapi in 2010. The research objective was to find the communication pattern of the Sleman Regency tourism office with local residents. tourism site. A qualitative approach, by conducting interviews, observation and data analysis. Groupthink Theory, which is a decision-making process that occurs in the manager of the Merapi Lava Tour and the Tourism Office. The results of this study indicate that the Tourism Office has maximally provided services, by not taking over tourism objects, instead the Tourism Office helps in collecting fees so that when there are things that are not desired, Jasa Raharja's insurance can apply when purchasing retribution tickets legally. The communication pattern carried out by the Tourism Office is indeed ineffective, because there is no clear flow between the Dinas and managers and community members.